Answer:
This contradicts the Mean Value Theorem since there exists a c on (1, 7) such that f '(c) = f(7) − f(1) (7 − 1) , but f is not continuous at x = 3
Step-by-step explanation:
The given function is
[tex]f(x)=(x-3)^{-2}[/tex]
When we differentiate this function with respect to x, we get;
[tex]f'(x)=-\frac{2}{(x-3)^3}[/tex]
We want to find all values of c in (1,7) such that f(7) − f(1) = f '(c)(7 − 1)
This implies that;
[tex]0.06-0.25=-\frac{2}{(c-3)^3} (6)[/tex]
[tex]-0.19=-\frac{12}{(c-3)^3} [/tex]
[tex](c-3)^3=\frac{-12}{-0.19}[/tex]
[tex](c-3)^3=63.15789[/tex]
[tex]c-3=\sqrt[3]{63.15789}[/tex]
[tex]c=3+\sqrt[3]{63.15789}[/tex]
[tex]c=6.98[/tex]
If this function satisfies the Mean Value Theorem, then f must be continuous on [1,7] and differentiable on (1,7).
But f is not continuous at x=3, hence this hypothesis of the Mean Value Theorem is contradicted.